Successful treatment of congenital pseudarthrosis of the tibia: still a challenge. - Bobotas, K; Lallos, S N; Nikolaou, V S; Kοrres, D S; Efstathopoulos, N E (Eur J Orthop Surg Traumatol, 2013)
The congenital pseudarthrosis of the tibia (CPT) is one of the most challenging problems in pediatric orthopedics. The primary treatment goals are outlined as osteosynthesis, stabilization of the ankle mortise by fibular stabilization and lower-limb-length equalization. Despite the fact that each of the aforementioned goals is difficult to be achieved regardless the surgical option, the main biological consideration is the same: pseudarthrosis resection, biological bone bridging of the defect by stable fixation and the correction of any angular deformity. The external fixation method is suggested as valuable treatment of CPT because it can address not only pseudarthrosis but also all complex deformities associated with this condition. However, treatment of CPT is impaired with complications due to the complex nature of the disease thus failure is common. The most common of these are refracture, growth disturbance, poor foot and ankle function with stiffness. Of these, refracture is the most common and serious complication after primary healing and might result in the reestablishment of pseudarthrosis. Therefore, an effective, safe and practical treatment method that minimizes the residual challenges after healing and accomplishes the multiple goals of treatment is needed. In this article, we report a patient with CPT treated successfully with external fixation. Level of evidence IV retrospective.
Keywords: Adolescent; Fracture Fixation, Internal; Humans; Ilizarov Technique; Male; Neurofibromatosis 1; Pseudarthrosis; Tibial Fractures